Histological Studies on the Prenatal Development of Endocrine Pancreas in Goats* - Sreeranjini, A. R.; Ashok, N.; Lucy, K. M.; Maya, S.; Chungath, J. J. (Indian Journal of Veterinary Anatomy, 2016)
The present study was conducted on the prenatal development of endocrine pancreas in goat foetuses. The development of endocrine pancreas was observed in goat embryos from 52 days of prenatal life. The endocrine cells appeared as large, solitary cells among the ductular cells. Along with the development of these cells in the ductular wall, a space developed in the mesenchyme around these cells. Later these cells increased in number and were pushed out of the ductular wall with corresponding increase in the size of the space. By 69 days of age, a few well defined encapsulated islets were observed and A-cells and B-cells could be identified. From 71 days onwards, lobulation of pancreatic parenchyma became evident and developing islets of varying size were noticed within lobules as well as in the interlobular connective tissue. Some islets showed blood-filled spaces among endocrine cells. Pancreas of 134 days old foetuses showed thick nerve bundles or peri-insular plexuses in close contact with islets located in the interlobular septa. From 140 days of development onwards, some of the large islets showed a central sinus. In 148 days-old foetuses, most of the large islets contained a large central sinus with peripherally arranged groups of cells or several small sinuses among groups or cords of cells.